Aspek Yuridis Renegosiasi Kontrak Karya di Indonesia (Studi Kontrak Karya Antara Pemerintah Republik Indonesia Dengan PT Freeport Indonesia) - Ratnasari Fajariyah Abidin (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
Mining is one of sources the country and religional incomes. That is why the presence of mining company truly help country and region /local development. Renegotiation is based on the acts number 4 year 2009 about mineral coal, of wich statement should be adjudted to the recent acts. The bill number 4 year 2009 stated the mining conservation based on utility, equality and nationality. The creation-contract negotiation has strong law foundation, even though its content clashes with the contarct which already been signed. Renegiatation does not deny the content of contract, but adption of current condiotion and the rules of certain country. It is imposible to keep the content compeletely the same after long years because that condition will be harmful for one side. Even worse that contract is full of political and foreign needs as the main consideration.